2015
DOI: 10.1002/2015gc005830
|View full text |Cite
|
Sign up to set email alerts
|

Tracing mantle‐reacted fluids in magma‐poor rifted margins: The example of Alpine Tethyan rifted margins

Abstract: The thinning of the crust and the exhumation of subcontinental mantle in magma‐poor rifted margins is accompanied by a series of extensional detachment faults. We show that exhumation along these detachments is intimately related to migration of fluids leading to changes in mineralogy and chemistry of the mantle, crustal, and sedimentary rocks. Using field observation and analytical methods, we investigate the role of fluids in the fossil distal margins of the Alpine Tethys. Using Cr‐Ni‐V, Fe, and Mn as tracer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(92 citation statements)
references
References 81 publications
5
85
0
2
Order By: Relevance
“…However, Jammes et al () and Masini et al () suggested that the Labourd massif might represent the western lateral prolongation of the basement located below the northern Mauléon basin. In this area, the authors described evidence for fluid and reaction assisted brittle fault rocks and associated tectonosedimentary breccias, diagnostic of extensional detachment faults in hyperextended settings (Jammes et al, ; Pinto et al, ; Tugend et al, ). The description of depositional contacts between Albo‐Cenomanian sediments and exhumed midcrustal granulites (Jammes et al, ) and the reworking of these granulites in the overlying sediments argue for laterally discontinuous and allochthonous pre‐rift cover sequences separated by exhumation windows (Figure ).…”
Section: Fossil Example Of Asymmetric Rift: Observations From the Arzmentioning
confidence: 99%
“…However, Jammes et al () and Masini et al () suggested that the Labourd massif might represent the western lateral prolongation of the basement located below the northern Mauléon basin. In this area, the authors described evidence for fluid and reaction assisted brittle fault rocks and associated tectonosedimentary breccias, diagnostic of extensional detachment faults in hyperextended settings (Jammes et al, ; Pinto et al, ; Tugend et al, ). The description of depositional contacts between Albo‐Cenomanian sediments and exhumed midcrustal granulites (Jammes et al, ) and the reworking of these granulites in the overlying sediments argue for laterally discontinuous and allochthonous pre‐rift cover sequences separated by exhumation windows (Figure ).…”
Section: Fossil Example Of Asymmetric Rift: Observations From the Arzmentioning
confidence: 99%
“…We use a friction coefficient of 0.01 to simulate a weak serpentinized mantle under high pore fluid pressure (Hilairet et al, 2007). Observations of exhumed serpentinized mantle in the Alps (Pinto et al, 2015) show that mantle serpentinization is of the order of 60%, and we decrease the density accordingly. For the continental crust, feldspar and wet quartz rheology are controlled by dislocation creep laws (Rybacki et al, 2008(Rybacki et al, , 2010 with a minimum viscosity of 10 19 Pa.s.…”
Section: 1029/2019gc008580mentioning
confidence: 99%
“…The multiphase and diachronous rift evolution resulted in a complex final crustal architecture that includes: a proximal 30‐km‐thick crust separated by a necking zone from a thinned continental crust (<10 km), followed by a wide transition zone between the continental and oceanic crusts where mantle exhumation occurred (Figure c). Importantly, no strong metamorphic overprint took place during the Alpine orogenesis allowing the primary sedimentary and geochemical features of the rock volumes to be preserved (Froitzheim & Manatschal, ; Manatschal, Marquer, & Frueh‐Green, ; Masini, Manatschal, Mohn, & Unternehr, ; Pinto et al, ).…”
Section: The Adriatic Continental Marginmentioning
confidence: 99%
“…The discovery of hydrothermal vents at present‐day mid ocean ridges, as well as the occurrence of widespread serpentinization processes, shed light on the relevance and spatial abundance of fluid activity in response to the late stage of continental rifting and early seafloor spreading (Edmonds, ; Harding et al, ; Kelley & Shank, ; Kuhn et al, ; McCaig, Cliff, Escartin, Fallick, & Macleod, ). Only recently, attention has been paid to the study of such activity in the more distal parts of the continental margins (Incerpi, Martire, Manatschal, & Bernasconi, ; Pinto, Manatschal, Karpoff, & Viana, ) i.e., where the pre‐mantle exhumation history is preserved. At present, only few ODP or IODP drill holes are available from such domains (e.g., Tucholke, Sibuet, & Klaus, ).…”
Section: Introductionmentioning
confidence: 99%